Ginsenoside Rg1 Improves Differentiation by Inhibiting Senescence of Human Bone Marrow Mesenchymal Stem Cell via GSK-3β and β-Catenin. (26th May 2020) - Wang, Ziling; Jiang, Rong; Wang, Lu; Chen, Xiongbin; Xiang, Yue; Chen, Linbo; Xiao, Minghe; Ling, Li; Wang, Yaping
Abstract : Objectives . To demonstrate the effect of Ginsenoside Rg1 on the differentiation of human bone marrow-derived mesenchymal stem cells (hBM-MSCs). Subsequently, a rational mechanism for the detection of Rg1 which affects mesenchymal stem cell differentiation was explored. Methods . Flow cytometry is used for cell identification. The differentiation ability of hBM-MSCs was studied by differentiation culture. SA- β -gal staining is used to detect cell senescence levels. Western blot and immunofluorescence were used to determine protein expression levels. RT-qPCR is used to detect mRNA expression levels. Results . Rg1 regulates the differentiation of hBM-MSCs. Differentiation culture analysis showed that Rg1 promoted cells to osteogenesis and chondrogenesis. Western blot results showed that Rg1 regulated the overactivation of the β -catenin signaling pathway and significantly adjusted the phosphorylation of GSK-3 β . GSK-3 β inhibitor (Licl) significantly increased Rg1-induced phosphorylation of GSK-3 β, which in turn reduced Rg1-induced differentiation of hBM-MSCs. Conclusion . Ginsenoside Rg1 can reduce the excessive activation of the Wnt pathway in senescent cells by inhibiting the phosphorylation of GSK-3 β and regulate the mesenchymal stem cell differentiation ability.